Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.est.0c04882
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Atmospheric Reactive Nitrogen Deposition Suppresses Biological Nitrogen Fixation in Peatlands

Abstract: Biological nitrogen fixation (BNF) represents the natural pathway by which mosses meet their demands for bioavailable/reactive nitrogen (Nr) in peatlands. However, following intensification of nitrogen fertilizer and fossil fuel use, atmospheric Nr deposition has increased exposing peatlands to Nr loading often above the ecological threshold. As BNF is energy intensive, therefore, it is unclear whether BNF shuts down when Nr availability is no longer a rarity. We studied the response of BNF under a gradient of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
(91 reference statements)
1
16
0
Order By: Relevance
“…This suppression was found to be close to the reduction in BNF (by 64%) caused by experimental fertilisation treatments in plots of Degerö Stormyr receiving 30 kg N ha −1 y −1 of Nr for more than 20 years. The magnitude of the suppression in BNF activity was shown to be higher in more pristine peatlands rather than bogs that have been exposed to long-term elevated Nr deposition (Saiz et al, 2021), as in the Migneint, and this could be ascribed to adaptations of the physiological response of the mosses to inorganic N supply. Specifically, it has been shown that Sphagnum is capable of regulating its uptake of ammonium, in a way that maximises N use efficiency while avoiding intoxication (Fritz et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This suppression was found to be close to the reduction in BNF (by 64%) caused by experimental fertilisation treatments in plots of Degerö Stormyr receiving 30 kg N ha −1 y −1 of Nr for more than 20 years. The magnitude of the suppression in BNF activity was shown to be higher in more pristine peatlands rather than bogs that have been exposed to long-term elevated Nr deposition (Saiz et al, 2021), as in the Migneint, and this could be ascribed to adaptations of the physiological response of the mosses to inorganic N supply. Specifically, it has been shown that Sphagnum is capable of regulating its uptake of ammonium, in a way that maximises N use efficiency while avoiding intoxication (Fritz et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Despite the relatively high atmospheric deposition of Nr above the critical load of 10 kg N ha −1 y −1 that in the long-term could favour the dominance of vascular plants over Sphagnum mosses (Dore et al, 2012), biological nitrogen fixation associated with mosses and in bulk surface peat (asymbiotic) has not completely shut down but accounted for~2% of the N inputs in the Migneint bog. Saiz et al (2021) have shown that BNF activity in the Migneint is suppressed by 69% compared to the more pristine Swedish Degerö Stormyr peatland receiving~2 kg N ha −1 y −1 of background Nr atmospheric deposition. This suppression was found to be close to the reduction in BNF (by 64%) caused by experimental fertilisation treatments in plots of Degerö Stormyr receiving 30 kg N ha −1 y −1 of Nr for more than 20 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Only through microbial action, can plants convert free nitrogen in the atmosphere into ammonia or other nitrogenous organic matter for their own growth, which is called biological nitrogen xation. 4,5 In nature addition, there is another method of nitrogen xation: under the action of lightning, N 2 is directly converted into NO, and then into NO 2 . This process is called high-energy nitrogen xation.…”
Section: Introductionmentioning
confidence: 99%